2017
DOI: 10.1136/sextrans-2016-052876
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hepatitis C testing in men who have sex with men, and associated risk behaviours, in Manchester, UK

Abstract: In this survey, HIV-positive MSM had significantly different drug use behaviour which may explain the higher HCV burden. However, HCV was also associated with HIV-negative MSM engaging in high-risk sexual practices. All MSM attending sexual health clinics must have a risk assessment and HCV screening should be offered based on the risk. Further studies are warranted to explore the interplay between HCV and HIV risk associated with drug use versus sexual practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 19 publications
5
25
1
Order By: Relevance
“…Two‐thirds of persons diagnosed as coinfected were diagnosed with HIV infection > 6 months before their HCV diagnosis, a significant proportion of whom had previously tested HCV negative, confirming the results of previous studies that identified continued behaviours following an HIV diagnosis that put individuals at increased risk of sexually transmitted infections, including HCV infection . While some HIV‐positive MSM modify their risk behaviour (serosorting or only having condomless anal sex with other HIV‐positive MSM) in an attempt to prevent onwards transmission , tackling the risk of HCV and other sexually transmitted infections remains a challenge for HIV and sexual health services.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two‐thirds of persons diagnosed as coinfected were diagnosed with HIV infection > 6 months before their HCV diagnosis, a significant proportion of whom had previously tested HCV negative, confirming the results of previous studies that identified continued behaviours following an HIV diagnosis that put individuals at increased risk of sexually transmitted infections, including HCV infection . While some HIV‐positive MSM modify their risk behaviour (serosorting or only having condomless anal sex with other HIV‐positive MSM) in an attempt to prevent onwards transmission , tackling the risk of HCV and other sexually transmitted infections remains a challenge for HIV and sexual health services.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the UK Collaborative HIV Cohort (UK CHIC) study estimated HCV prevalence for HIV‐positive persons in 2011 at 10.0% overall, corresponding to an estimated 10 000 people, and 9.9% in HIV‐positive MSM, compared with 83.3% in HIV‐positive PWID . However, these estimates, along with those from other studies , have used HIV‐infected individuals as the base population and there has been less focus on HIV prevalence among persons who are HCV positive in the UK. Dougan et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guidelines on who to test for hepatitis C in sexual health services are available, and often risk‐factor based . In either case, in order to achieve elimination in high‐risk populations such as men who have sex with men, primary prevention and the prevention of reinfection will play a major role .…”
Section: Wherementioning
confidence: 99%
“…A study of hepatitis C acquisition confirms high rates of drug use and also of fisting and group sex among those newly diagnosed, with a complex interplay between drug use and sexual practices which differs between HIV negative and HIV positive men 7. Clinicians will be fascinated and concerned by Harrison et al’s study of genital Neisseri a isolates, which demonstrates anal and urogenital hyperinvasive meningococci and multi-resistant gonococci in hospitalised MSM 8.…”
mentioning
confidence: 97%